O sentido do trabalho escolar nos anos finais do Ensino Fundamental e suas relações com a organização escolar - Nascimento, Débora Baroudi (2021)
The democratization of the school occurred paradoxically, compromising the school system with the reproduction of social inequalities, in a context in which it promised exactly the opposite. The lack of meaning in school work is one of the factors resulting from this process. It is possible to understand that changes in school culture, based on instrumental rationality and the utilitarian relationship with knowledge, contributed to the loss of meaning in school work for teachers and students. As a result of this context, there are among teachers who demonstrate frustration and dissatisfaction with their work, and students who express disinterest and alienation with the school in general and with the classes in particular. Taking the school as the object of analysis (NÓVOA, 1992), this research understands that the school organization in its physical, administrative, and social aspects, that is, in its organizational culture, also influences the expressions of interest and disinterest of teenage students. Guided by the concept of interactive learning (CANÁRIO, 2006) and by the understanding of school as an interlacing of cultures (PÉREZ GÓMEZ, 2001), this research investigated to what extent another school organization can engender attitudes of interest in teenage students. Through questionnaires, with open and closed questions, addressed to the management team, teachers and students in the final years of elementary school, it was found that changes in school reorganization positively changed school relations, expressed in the approximation between teacher-student; the pedagogical work and the teacher planning organized collectively; the participation and engagement of students in carrying out the activities. The data also reveal an understanding of interested students restricted to the particular motive and the extrinsic sense, far from being stimulated by the intellectual act of learning (LEONTIEV, 1961; CHARLOT, 1996; 2013). Student disinterest is perceived as an isolated factor, attributed to the student or the teacher, discrediting the school and the proposed organization model